Produção e avaliação de cerveja artesanal contendo tamarindo (Tamarindus indica L) - Silva, Augusto de Souza da (2020)
There has been a growing interest in craft and specialty beers in several countries. In addition to this factor, beer consumers are becoming increasingly demanding for products with sensory appeal, while looking for higher quality and lower price. The inclusion of fruits in beers guarantees a residual sweetness, aroma and characteristic flavor and increases its sensory appeal due to a greater range of aromatic compounds. Tamarind is an adjunct option in the incorporation of beers, being a fruit that has little exploitation and technological use in the food area. Aiming at this new demand for craft beers, the objective of the present work was to produce and evaluate the incorporation of tamarind pulp (Tamarindus indica L.) in the process of producing a craft beer. In the first stage of development of the work, the addition of tamarind pulp (15 g/L) was evaluated against two different stages of the process (fermentation and maturation), where through a sensory analysis the beer with tamarind pulp added at maturation presented better results, being carried out with consumers and craft beer makers (Tuckey test, at the 5% significance level). With the maturation chosen as the best stage for the addition of tamarind, the second stage of the study sought to evaluate three different concentrations of tamarind pulp (20, 40 and 60 g/L), with physical-chemical analyzes; phenolic compounds, sugars and organic acids by HPLC, FTIR; volatile microbiological analyzes by HS-SPME-GC-MS and sensory analysis. Sensory analysis sought to understand the behavior of this new product towards consumers who do not have the habit of consuming craft beers. All results were evaluated by ANOVA and the means compared to each other by the Tuckey test, at the level of 5% of significance. For the second formulation, the beers with the highest concentrations of tamarind pulp (CTM 40 and 60 g/L) obtained the most negative comments regarding the sensorial analysis of these samples, an excessively acidic flavor was attributed which did not please, on the other hand, the insertion of 20 g/L (CTM 20 g/L) showed good results compared to the tasters, where they attributed this refreshing, fruity and citrus character. The chemical classes of esters, alcohols and organic acids were the most prominent in the face of the identification of volatile compounds present in beers. From the results obtained, it can be concluded that the production of beers with tamarind pulp is a possible alternative for the use of this fruit.